Iron Activation of Natural Aluminosilicates to Remove Arsenic from Groundwater - Botto, Irma Lía (2013)
Low-cost adsorbents constituted by Fe-modified-aluminosilicates (laminar and zeolite type minerals) were developed and characterized to be used in the arsenic removal from groundwater. Iron activation was carried out “in situ” by the synthesis and deposition of mesoporous ferrihydrite. Natural iron-rich aluminosilicate was used as reference. All samples were characterized by X-ray diffraction, Raman spectroscopy, BET N2-adsorption, SEM-EDS microscopy and ICP chemical analysis. Experimental results of arsenic sorption showed that iron-poor raw materials were not active, unlike iron activated samples. The iron loading in all activated samples was below 5% (expressed as Fe2O3), whereas the removal capacity of these samples reaches between 200-700 µg of As by g of adsorbent, after reusing between 17 cycles and 70 cycles up to adsorbent saturation. Differences can be associated to mineral structure and to the surface charge modification by iron deposition, affecting the attraction of the As-oxoanion. On the basis of low-cost raw materials, the easy chemical process for activation shows that these materials are potentially attractive for As(V) removal. Likewise, the activation of clay minerals, with natural high content of iron, seems to be a good strategy to enhance the arsenic adsorption ability and consequently the useful life of the adsorbent.